Hybrid Electrocoagulation–Adsorption Process for Montelukast Sodium Removal from Water - Sayedali Mirkhalafi; Khalid S. Hashim; Osamah Al-Hashimi; Ali Majdi (Clean Technologies)
This study addresses the significant environmental challenge of pharmaceutical pollutants by demonstrating the effectiveness of a hybrid electrocoagulation–adsorption (EC-A) technique for removing Montelukast Sodium (MS) from contaminated water. The research was conducted in three stages—adsorption, electrocoagulation, and adsorption using the residual water from the electrocoagulation process. The adsorbent materials were characterised using various analytical techniques: X-ray Diffraction (XRD) for determining the crystalline structure, Energy-Dispersive X-ray Spectroscopy (EDX) for elemental composition, Scanning Electron Microscopy (SEM) for surface morphology, and Fourier Transform Infrared Spectroscopy (FTIR) for identifying functional groups before and after interaction with the pollutants. The adsorption phase achieved optimal results at a pH of 3 and a contact time of 120 min, with a maximum removal efficiency of 99.5% for a starting MS concentration of 50 mg/L using Calcium Ferric Oxide–Silica Sand (CFO-SS) adsorbent. The electrocoagulation phase showed a 97% removal efficiency with a pH of 11, a current density of 20 mA, and a 5 mm electrode distance, achieved in just 20 min. Finally, the combined EC-A process, with the pH of residual water adjusted to 3, further enhanced the removal efficiency to 74%, highlighting the method’s potential for pharmaceutical contaminant removal. These findings underscore the potential of the EC-A technique as a highly effective and adaptable solution for mitigating pharmaceutical contaminants in water.